Chitosan-Integrated Curcumin-Graphene Oxide/Copper Oxide Hybrid Nanocomposites for Antibacterial and Cytotoxicity Applications - Anandhavelu Sanmugam; Logesh Kumar Sellappan; Abbishek Sridharan; Swathy Manoharan; Ananda Babu Sairam; Abdulrahman I. Almansour; Subha Veerasundaram; Hyun-Seok Kim; Dhanasekaran Vikraman (MDPI AG, 2024)
This study deals with the facile synthesis of a single-pot chemical technique for chitosan-curcumin (CUR)-based hybrid nanocomposites with nanostructured graphene oxide (GO) and copper oxide (CuO) as the antibacterial and cytotoxic drugs. The physicochemical properties of synthesized hybrid nanocomposites such as CS-GO, CS-CuO, CS-CUR-GO, and CS-CUR-GO/CuO were confirmed with various advanced tools. Moreover, the in vitro drug release profile of the CS-CUR-GO/CuO nanocomposite exhibited sustained and controlled release during different time intervals. Also, the antibacterial activity of the CS-CUR-GO/CuO hybrid nanocomposite presented the maximum bactericidal effect against Staphylococcus aureus and Escherichia coli pathogens. The hybrid nanocomposites revealed improved cytotoxicity behaviour against cultured mouse fibroblast cells (L929) via cell adhesion, DNA damage, and proliferation. Thus, the chitosan-based hybrid nanocomposites offer rich surface area, biocompatibility, high oxidative stress, and bacterial cell disruption functionalities as a potential candidate for antibacterial and cytotoxicity applications.